Paradigm Shift of Beauty In Landscape Design: Strategies Towards 'Big Foot’ Aesthetic - Pramanti, Lucia Indah (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2017)
Human perception about beauty always mirrors civilization, and is embodied in their built environment. In other words, what people sees as beautiful plays a crucial role towards how nature/landscape is developed. This paper intentions are to rethink on contemporary aesthetic value in landscape design, to evaluate current aesthetic paradigm, and to find landscape design strategies that can promote sustainable goals. Using qualitative method, this paper first shows historical review on how landscape form through many centuries in both western and eastern civilization. Later, it examines on how contemporary landscapes are built. In the discussion, it is found that -using Chinese foot binding tradition as a metaphor– our contemporary landscape is designed to be unusable, unhealthy, unproductive ‘small feet’. Landscape is designed with beautification – merely for visual properties, not for human activity, destructing the natural properties of landscape, and too difficult to maintain. Human should be able to interact with the nature in landscape in order to create a behavioral changes towards the nature. As a conclusion, we need to shift our paradigm of beauty towards healthy ‘big foot’ aesthetic to be a direction on how to achieve the sustainable beauty. This ‘big foot’ aesthetic can be relevant not only in landscape design, but also in other fields related to the built environment. Keywords: landscape design, sustainability, green design, aesthetic value